Influence of Baseline Diastolic Blood Pressure on the Effects of Systolic Blood Pressure Lowering on Cognitive Function in Type 2 Diabetes Mellitus. (13th October 2022) - Gupta, Aditi; Boucher, Robert; Wei, Guo; Gronseth, Gary; Parks, Adam; Beddhu, Srinivasan
Abstract: Background: Lowering of systolic blood pressure (SBP) in patients with low diastolic blood pressure (DBP), can further lower DBP. This can potentially decrease cerebral perfusion and cognition. We examined the influence of baseline DBP on the effect of lowering SBP on cognition. Methods: This is a post hoc analysis of the Memory in Diabetes (MIND) substudy ( N = 1, 430) of the Action to Control Cardiovascular Risk in Diabetes (ACCORD) study (NCT00000620). Standard neuropsychological tests (Digit Symbol Substitution Test [DSST], Mini-Mental State Examination [MMSE], Rey Auditory Verbal Learning Test [RAVLT], and Stroop test) were performed at baseline and months 20 and 40. We compared the effects of intensive (goal SBP <120 mm Hg) vs. standard (goal SBP <140 mm Hg) SBP control on the changes in the 4 test scores from baseline to the averages of months 20 and 40 across the range of baseline DBP using cubic spline terms. Results: Mean age was 63 ± 6 years, 55% were women and 66% White. Participates with lower baseline DBP were older, had more cardiovascular events and a longer duration of diabetes. There was no difference in the change in DSST (−0.22; 95% CI −0.97, 0.52), MMSE (−0.14; 95% CI −0.34, 0.06), RAVLT (−0.12; 95% CI −0.29, 0.06), and Stroop interference (−0.47; 95% CI −1.76, 0.82) in the intensive vs. standard SBP intervention. There was no interaction between baseline DBP and change in scores with the SBP intervention. Conclusions: Intensive SBP reduction does not adversely affect cognition, even in those with low baseline DBP.